Click, clack, moo : cows that type - Cronin, Doreen; Lewin, Betsy (New York : Simon & Schuster Books for Young Readers, 2000)
When Farmer Brown's cows find a typewriter in the barn they start making demands, and go on strike when the farmer refuses to give them what they want.
Keywords: Cows -- Fiction; Domestic animals -- Fiction; Typewriters -- Fiction